Tinjauan Yuridis Pengaturan Pidana Pokok dan Tujuan Pemidanaan dalam KUHP 2023 Indonesia dan Strafgesetzbuch Jerman (International Forum of Researchers and Lecturers, 2025)
The development of Indonesian criminal law underwent a significant transformation through the enactment of the 2023 Criminal Code, which replaced the Dutch colonial legacy and adopted a humanist-restorative punishment paradigm. This study analyzes the comparison between the Indonesian Criminal Code 2023 and the German Strafgesetzbuch (StGB), particularly in the structure of the main punishment and the purpose of punishment, to evaluate the suitability of the concept with modern judicial practices. The normative research method with a statutory and conceptual approach reveals that the 2023 Criminal Code expands the types of basic punishment, such as imprisonment, closure, supervision, fines, and community service, to diversify punishment that reduces dependence on prisons and supports social reintegration. However, the nominal category-based fine system still has the potential to create economic inequality, in contrast to Germany, which uses a day-fine system that is adjusted to the economic capacity of the offender. While Germany relies on suspended sentences and structured rehabilitation programs, Indonesia still faces challenges in the implementation of alternative punishments such as closure, which lack parameters and practices. Both countries' sentencing objectives emphasize community protection and rehabilitation, but Germany is more mature in its integration of the principle of proportionality, assessment of subjective offender factors, and supporting infrastructure. This research recommends reforming Indonesia's fine system by adopting a day-fine mechanism, developing technical guidelines for alternative punishment, strengthening rehabilitation programs, and harmonizing policies to improve economic justice and the effectiveness of punishment. The findings are expected to be a reference in improving the Criminal Code 2023 before its full implementation in 2026, so that the Indonesian criminal justice system is more responsive, fair, and in line with the values of Pancasila and modern legal principles.